Evaluasi Proses Pemberian Feedback di Tutorial Problem-Based Learning di Fakultas Kedokteran - Tezar Samekto Darungan; Gandes Retno Rahayu; Mora Claramita (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2016)
Background: Feedback constitutes one of the important components in student Since feedback is not solely limited to student assignments, it can also be given during student learning, including tutorials. Therefore, the institution should pay particular attention to the process of feedback provision one of which is through evaluations on the process of providing feedback in tutorials. This study aimed to evaluate the process of providing feedback on the Problem-Based Learning tutorials in the Faculty of Medicine, Universitas Islam Sumatera Utara.Method: This study used mixed methods with a quantitative method performed first, followed by a qualitative method with a phenomenology approach. The subjects were the undergraduate medical students of the class of 2012 and tutors of the Problem-Based Learning tutorials. The quantitative data analysis was done by the descriptive analysis while the qualitative data analysis was done through verbatim analysis, coding, categorization and conclusion.Results: The students had received feedback but not routinely. Both the students and the tutors had perceived that feedback was important and gave them many benefits. In practice, feedback was given on the basis of tutors’ direct observation results. Action ;plan was often given but rarely involved discussion. Self-assessment/reflection was also not a matter of routine and the tutors did not know that it was part of the feedback. The contents of feedback were more often in the form of general comments. Feedback was often communicated in one direction. The students’ response to feedback varied. In giving and receiving feedback, the students, the tutors, the tutorial activities and the content of the feedback itself could influence one another. The students had  preferences so feedback can be more easily accepted and they focused on the structural aspects of feedback (the frequency of giving feedback, the detail and spesific feedback, two way communication in giving feedback and the feedback target). Tutors expected more trainings in giving feedback provided by institution to tutors and students.Conclusion: Despite its valuable benefits, tutorial feedback in the Faculty of Medicine, Universitas Islam Sumatera Utara,is still not in accordance with the principle of providing feedback and many factors have affected this condition.